1985
DOI: 10.1177/00220345850640120901
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Retention of Aluminum by Dental Enamel

Abstract: The uptake, depth of penetration, and retention of aluminum (Al) in sound and acid-etched dental enamel were determined following in vitro applications of solutions containing 0.005 M or 0.037 M Al. Compared with controls, significant amounts of Al uptake (approximately 2000 to 6000 ppm) were detected in both sound and etched enamel, with significantly more Al deposited in the latter. Analysis of successive layers of treated enamel demonstrated that Al was located predominantly within the first 20 microns of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…9 It has been shown that enamel treated with AlCl 3 solution for 20 minutes could uptake aluminum (Al) from the solution, especially within the first 20 µm of enamel. 20 Moreover, this AlCl 3 treated enamel revealed inhibition of the demineralization process of hydroxyapatite (HAP), which was exposed to a demineralizing solution, [21][22] even though the Al concentration was as low as 0.1 µmol/l. 23 This mechanism has been explained by displacement of calcium in the HAP by Al, which results in the very insoluble Al (OH) 2 H 2 PO 4 compound.…”
Section: Groupsmentioning
confidence: 92%
“…9 It has been shown that enamel treated with AlCl 3 solution for 20 minutes could uptake aluminum (Al) from the solution, especially within the first 20 µm of enamel. 20 Moreover, this AlCl 3 treated enamel revealed inhibition of the demineralization process of hydroxyapatite (HAP), which was exposed to a demineralizing solution, [21][22] even though the Al concentration was as low as 0.1 µmol/l. 23 This mechanism has been explained by displacement of calcium in the HAP by Al, which results in the very insoluble Al (OH) 2 H 2 PO 4 compound.…”
Section: Groupsmentioning
confidence: 92%
“…6 It has been reported that enamel treated with AlCl 3 solution for 20 minutes has the potential to take up aluminum from the solution, especially within the first 20 µm. 8 In addition, this AlCl 3 -treated enamel inhibits demineralization of hydroxyapatite (HAP), exposed to a demineralizing agent. 9,10 This mechanism has been explained by replacement of calcium in the HAP by aluminum, resulting in the formation of Al(OH) 2 H 2 PO 4 , which is insoluble.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into the cariostatic mechanism for Al have demonstrated that topical treatment with Al solutions in creased the resistance of enamel to acid dissolution [Adler and Csoban, 1948;Manly and Bibby, 1949;Putt and Kleber, 1985;Matsuo et al, 1987] and deposited Al in the surface enamel [Clarkson, 1976;Kleber and Putt. 1985].…”
mentioning
confidence: 99%
“…Inves tigations with F indicate that repeated applications with low concentrations of F are more beneficial than single treat ments with high F concentrations [Poulsen and Larsen, 1975;Ericsson, 1977;Fejerskov et al, 1981;Wei, 1985;Bel tran and Burt, 1988]. Also, Kleber and Putt [1985] showed that 4 consecutive 5-min applications with a 'suboptimum ' Al concentration, similar to dietary exposure and accumu lation, resulted in more uptake of Al by enamel than a single 20-min exposure with a 7-fold greater Al concentration.…”
mentioning
confidence: 99%